2004
DOI: 10.1103/physrevlett.93.090602
|View full text |Cite
|
Sign up to set email alerts
|

Universality of the Shear Viscosity from Supergravity Duals

Abstract: Kovtun, Son, and Starinets proposed a bound on the shear viscosity of any fluid in terms of its entropy density. We argue that this bound is always saturated for gauge theories at large 't Hooft coupling, which admit holographically dual supergravity description.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
634
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 493 publications
(680 citation statements)
references
References 19 publications
45
634
1
Order By: Relevance
“…One may be surprised that the shear viscosity is not greater than or equal to 1/4π. The reason is that the theorem of [55] is not applicable because R 0 0 = R x x . Instead, in this version of the soft wall model, one finds by explicit computation that…”
Section: Gauge/gravity Correspondencementioning
confidence: 99%
“…One may be surprised that the shear viscosity is not greater than or equal to 1/4π. The reason is that the theorem of [55] is not applicable because R 0 0 = R x x . Instead, in this version of the soft wall model, one finds by explicit computation that…”
Section: Gauge/gravity Correspondencementioning
confidence: 99%
“…In [6], these authors computed the shear viscosity η of strongly-coupled N =4 super-Yang-Mills (SYM) theory in 3 + 1 dimensions and at finite temperature. They found that the ratio of shear viscosity to entropy density equals 1/4π, a result that was later argued to be universal, in the sense that it applies to any gauge theory described by a supergravity dual, in the limit of large 't Hooft coupling [8]. 1 These results raised the tantalizing possibility of using AdS/CFT to study the QGP.…”
Section: Introductionmentioning
confidence: 99%
“…P = ε/3 and ζ = 0 follow just from conformal invariance. 4πη/s = 1 for the fluid in any non-Abelian gauge theory with a dual gravitational description, in the strong coupling and large-N c limit [34][35][36][37]. Note that the stress-energy tensor depends on symmetric combinations of the fluid gradients ∂ α u β and is independent of the fluid vorticityω…”
Section: Gravitational Description Of a Moving Fluidmentioning
confidence: 99%